1998
DOI: 10.1029/98jb02409
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional upper crustal heterogeneity and anisotropy around Hole 504B from seismic tomography

Abstract: Abstract. We have used over 16,000 compressional wave travel times recorded on 11 ocean bottom seismometers to determine the magnitude of P-wave heterogeneity and anisotropy in the upper 2 km of the oceanic crust in an -• 150 km 2 area around Hole 504B, the deepest hole drilled into the oceanic crust. Our best fitting one-dimensional, isotropic upper crustal velocity model for the 150 km 2 area around the drill site is similar to velocity models at Hole 504B determined using downhole sonic logs, vertical seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
1
35
3
Order By: Relevance
“…Activesource seismic studies are not usually designed with the intent to measure three-dimensional variations in anisotropy, but the results thus far are encouraging. Several studies have examined one-dimensional depth-dependent anisotropy in oceanic crust, including measurements along mid-ocean ridge crests (Caress et al, 1992;MacDonald et al, 1994;Sohn et al, 1997;Barclay et al, 1998;Dunn and Toomey, 2001;Barclay and Wilcock, 2004;Tong et al, 2004;Seher et al, 2010), in older oceanic crust (>1 Ma) (Stephen, 1981(Stephen, , 1985White and Whitmarsh, 1984;Shearer and Orcutt, 1986;Detrick et al, 1998), and in back-arc basins (Hirata et al, 1992). Few prior studies have attempted to extract lateral variations in crustal anisotropy at a spreading center (e.g., Sohn et al, 1997;Dunn and Toomey, 2001;Weekly et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Activesource seismic studies are not usually designed with the intent to measure three-dimensional variations in anisotropy, but the results thus far are encouraging. Several studies have examined one-dimensional depth-dependent anisotropy in oceanic crust, including measurements along mid-ocean ridge crests (Caress et al, 1992;MacDonald et al, 1994;Sohn et al, 1997;Barclay et al, 1998;Dunn and Toomey, 2001;Barclay and Wilcock, 2004;Tong et al, 2004;Seher et al, 2010), in older oceanic crust (>1 Ma) (Stephen, 1981(Stephen, , 1985White and Whitmarsh, 1984;Shearer and Orcutt, 1986;Detrick et al, 1998), and in back-arc basins (Hirata et al, 1992). Few prior studies have attempted to extract lateral variations in crustal anisotropy at a spreading center (e.g., Sohn et al, 1997;Dunn and Toomey, 2001;Weekly et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Layer 2/3 boundary is present in the depth range 1.2-1.5 km subbasement. Velocity model of Detrick et al (1998) for Site 504, also based on ocean-bottom hydrophone refraction, is shown for comparison. Apparent differences are dominated by differences in inversion techniques, but differences at 1.3-1.7 km may be barely above uncertainty.…”
Section: Unit 1256d-95: Cryptocrystalline Aphyric Basaltmentioning
confidence: 99%
“…The textbook explanation relating layer 3 velocities to the presence of gabbro was ruled out as the location of the boundary was proposed to be located either within or at the top of the sheeted-dike complex of the only really deep hole ever drilled into modern oceanic crust, Deep Sea Drilling Project (DSDP) and Ocean Drilling Program (ODP) Hole 504B (Cann, Langseth, et al, 1983;Anderson, Honnorez, et al, 1985;Becker, Sakai, et al, 1988;Dick, Erzinger, et al, 1992;Alt, Kinoshita, et al, 1993). This result was obtained by combining a series of constraints on the velocity structure of the upper crust (Alt, Kinoshita, et al, 1993;Hobart et al, 1985;Collins et al, 1989;Swift et al, 1998a;Detrick et al, 1998). As a consequence, the boundary was found to stand at least 400 m, possibly up to 800 m, above yet unsampled gabbroic rocks previously believed to correspond to layer 3 seismic velocities.…”
Section: Introductionmentioning
confidence: 82%